The prevalence and correlates of biomarker positive unhealthy alcohol use among women living with and without HIV in San Francisco, California. - Jennifer P Jain; Yifei Ma; Carol Dawson-Rose; Glenn-Milo Santos; Alvina Han; Jennifer Price; Judith A Hahn; Phyllis C Tien (PLoS ONE)
The objective of this study was to identify the prevalence and correlates of phosphatidylethanol (PEth) levels suggestive of unhealthy alcohol use among women living with and without HIV who self-reported no or low-risk drinking. We analyzed data from a cross-sectional study among women enrolled in the San Francisco Bay Area site of the Women's Interagency HIV Study (WIHS). Between October 2017 and March 2018, PEth was tested from dried blood spots in 192 women enrolled in the San Francisco site of the WIHS. Using multivariable logistic regression, we identified the correlates of PEth levels suggestive of unhealthy alcohol use (>50 ng/ml) among the 168 women who reported no or low-risk drinking (<7 drinks per week) in the past six months, while controlling for age in years and race/ethnicity. Among the 168 women in the analysis sample, the median age was 55; 51% identified as Black/African American, 47% were living with HIV and 28% had PEth levels ≥50 ng/ml which are suggestive of unhealthy alcohol use. Factors independently associated with PEth levels ≥50 ng/ml in adjusted models were: identifying as Black/African American (adjusted odds ratio [aOR] = 8.34, 95% CI = 2.06-33.72), having an alanine transaminase to aspartate aminotransferase ratio > 1 (aOR = 3.10, 95% CI = 1.18-8.13), higher high-density lipoprotein levels (aOR = 1.31 per 10 mg/dL increase, 95% CI = 1.01-1.70), and consuming a greater number of drinks per week in the past six months (aOR = 1.40, 95% CI = 1.10-1.78). Nearly a third of women in this study had PEth levels suggestive of unhealthy alcohol use and potentially under-reported their use. To optimize alcohol related health care, there is a need to consider approaches to improve ascertainment of unhealthy alcohol use, especially among Black/African American women and those living with liver disease, so that interventions can be initiated.